Dilemma in Merantau Tradition and Culture in Minangkabau for Adult Men Viewed Through Symbolic Interactionism - Hadibroto, Joko Utomo; Noermansyah, Azriel Adam; Novanski, Bintang Zamani; Alfandi, Muhammad Nur (Universitas Wiralodra, 2023)
This research is entitled Dilemma in Merantau Tradition and Culture in Minangkabau for Adult Men Viewed Through Symbolic Interactionism. The tradition and culture of migrating - especially in Minangkabau, West Sumatra - is unique and distinctive. This is marked by the existence of literary works in the form of rhymes, rules, and customary norms, which contain the need to go abroad. The tradition and culture of migrating in Minangkabau is obligatory for adult men to leave their hometown. The goal is to be able to live independently and be able to adapt to their new environment. However, there are also some adult men who do not migrate for certain reasons. This becomes a dilemma, namely, choose (choose) to migrate or not to migrate. Through the study of symbolic interactionism theory, the author tries to reveal the dilemmatic problem for adult men, when each of them has reasons to choose between two options. Although the obligation to wander is a law or customary regulation that has been going on for generations. In fact, wandering or not migrating does not matter, when each individual has reasons that support his choice